Investigation of the Supply Chain Management Effects on Tourism Infrastructure in the Region as a Competitive Factor - Liliya Raisovna Fakhrutdinova; Boris Mojshevich Eidelman; Oleg Aleksandrovich Bunakov (International Journal of Supply Chain Management, 2019)
Abstract- In this paper the components of tourism infrastructure were investigated by considering the supply chain management effects. One of the most important components of tourism infrastructure is the hotel industry. In recent years the quantity of means of collective placement in the Republic of Tatarstan increased. In the republic means of placement of almost all categories are presented, among them there are also representatives of such large hotel chains as Hilton, Marriott, ark Inn, Ramada, Ibis. The food industry is also an integral part of tourism infrastructure of the region. The show business of the Republic of Tatarstan covers a huge range of opportunities for visitors, beginning with excursion tours on historical, architectural and cultural sights, finishing with a possibility of visit of various festivals. Today the most important component of tourist infrastructure is transport infrastructure. Its importance and the importance is that first of all for the tourist it is necessary quickly and with comfort to reach a certain destination. Often an opportunity without special waste of time to reach the appointed place acts as criterion for selection of the place of a trip. As for the Republic of Tatarstan, it possesses an extensive transport network and includes all means of transport. The advantageous geographical location also contributes to the development of transport infrastructure. Public authorities of the republic also pay attention to development of the transport system. The Ministry of Transport and Road Facilities of the Republic of Tatarstan adopted the State program "Development of the transport system to the Republic of Tatarstan for 2014 - 2022" which purpose is ensuring further development and creation of a modern transport complex. Tourism in the Republic of Tatarstan in recent years became one of the most dynamically developing branches of economy. Carrying out a large number of actions of the international level and favorable investment climate allowed the republic to come to the leading position in development of tourism in the Russian Federation.